2021
DOI: 10.1017/s135561772100134x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Self-Reported Concomitant Depressive and Anxiety Symptoms and the Post-Concussion Symptoms Scale (PCSS)

Abstract: Objectives: The current study explored how affective disturbances, particularly concomitant anxiety and depressive symptoms, impact baseline symptom self-reporting on the Post-Concussion Symptoms Scale (PCSS) in college athletes. Methods: Athletes were separated into four groups (Healthy Control (HC) (n = 581), Depression Only (n = 136), Anxiety Only (n = 54), Concomitant Depression/Anxiety (n = 62)) based on their anxiety and depression scores. Groups were compared on Total PCSS Score a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
2
14
1
Order By: Relevance
“…These results support previous literature finding associations between postconcussion-like symptoms, preexisting health conditions, and mental health symptoms (Champigny et al, 2020; Garden & Sullivan, 2010; Thomas et al, 2021). This study reinforces previous findings and adds a deeper level of interpretation by comparing item and factor level endorsement rates, as well as exploring the relationship with academic self-efficacy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results support previous literature finding associations between postconcussion-like symptoms, preexisting health conditions, and mental health symptoms (Champigny et al, 2020; Garden & Sullivan, 2010; Thomas et al, 2021). This study reinforces previous findings and adds a deeper level of interpretation by comparing item and factor level endorsement rates, as well as exploring the relationship with academic self-efficacy.…”
Section: Discussionsupporting
confidence: 92%
“…The hypothesis was that postconcussion-like symptoms would be higher among those screening positive for depression or anxiety than those with a remote SRC history. This hypothesis follows the logic that after acute recovery from concussion, persistent symptoms may be attributable to other often preexisting conditions, such as mental health disorders (Iverson et al, 2015; Thomas et al, 2021). As an exploratory aim, the relationship between postconcussion symptoms and academic self-efficacy was also investigated.…”
mentioning
confidence: 99%
“…While prior work has shown that anxiety may lead to an increase in postconcussion-like symptoms at baseline and postconcussion (Balasundaram et al, 2016; Broshek et al, 2015; Edmed & Sullivan, 2012; Thomas et al, 2021), our study demonstrated that athletes reporting significant anxiety symptomatology did not experience a symptom exacerbation over the course of a baseline assessment. It may be that anxiety symptomatology does not make an athlete more susceptible to exacerbation under conditions of cognitive exertion.…”
Section: Discussioncontrasting
confidence: 82%
“…Notably, one of the strongest predictors of postconcussion anxiety is a history of prior mental health conditions (Sandel et al, 2017). Additionally, anxiety is often associated with an increased number of self-reported symptoms on common postconcussion symptom rating scales both in nonconcussed athletes at baseline (Balasundaram et al, 2016; Edmed & Sullivan, 2012; Thomas et al, 2021) and following a concussion (Aarts et al, 2015; Broshek et al, 2015). Given the relationship between mood (i.e., depression and anxiety) and postconcussion-like symptom reporting in nonconcussed athletes, these mood factors are prime candidates for exploring a potential relationship between increased postconcussion-like symptoms over the course of a comprehensive neuropsychological test battery.…”
Section: Current Studymentioning
confidence: 99%
“…The present study was predicated upon previous research showing that athletes experiencing comorbid depression and anxiety at baseline demonstrated significantly poorer neurocognitive performance (Thomas et al, 2022) and reported elevated symptomatology on the PCSS, both in terms of total score and symptom cluster scores, compared to athletes without mood disturbance at baseline (Thomas et al, 2021). Given that this neuropsychological profile is similar to what one might expect for athletes who recently sustained concussion, it is critical that we understand the ways in which mood disturbance at baseline might skew postconcussion comparisons.…”
Section: Discussionmentioning
confidence: 99%